Determination of zinc and copper in fertilizers by atomic absorption spectrophotometry - Alcarde, J. C.; Ponchio, C. O. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1972)
The determinations of zinc and copper in fertilizers by atomic absorption spectrophotometry are not influenced by the concentration of HC1 in the extracts, in the range of 0,1 N to 0,5 N and neither by the anions phosphate, sulfate and nitrate in the same range of HC1 concentration. The methods are precise and accurate for the determinations of zinc and copper in fertilizers.